THE DILEMMA OF COSTS ON BUSINESS SERVICES - Choy Zevallos, Elsa Esther (2012)
In recent decades, the service sector has maintained a steady growth in the economy of our country, so that a significant percentage of the workforce is employed in these companies that have specific characteristics. However, when it comes to the information costs, it is closely linked to the manufacturing industry and there is a wealth of information, while the service sector provides little information. It is important to establish a theoretical framework that allows us to conceptualize service companies and its characteristics, and then focus on the costs and models for the services sector.